Comparison of the Diet Photograph Record to Weighed Dietary Record and 24 h Dietary Recall for Estimating Energy and Nutrient Intakes Among Chinese Preschoolers - Xu, Yujie; Duan, Ruonan; Feng, Ping; Gao, Wanke; Xing, Dong; Cheng, Guo (Frontiers in Nutrition, 2021)
This study aimed to assess the relative validity of the diet photograph record (DP) for measuring energy and nutrient intakes against the weighed dietary record (WD) and the 24h dietary recall (HR) in Chinese preschoolers. Forty preschool children aged 4 to 6 years and their parents were recruited from a kindergarten in southwest China. Dietary intake of preschoolers on a same day, as estimated by the DP and the HR were compared with the WD. These three methods were administered by three group of investigators independently. The mean differences, correlation coefficients, cross-classifications and weighted κ, as well as the Bland-Altman plots were performed to assess the differences and agreements between estimates from the DP, the HR and the WD. For the DP and the HR, estimates of energy and nutrient intakes were moderate to high correlated with the WD, with higher coefficients ranging from 0.73 to 0.94 for the DP. Both methods tended to underestimate the dietary intake, but the differences from known weights using the DP were significantly smaller than those using the HR. The weighed κ values ranking the preschoolers ranged from 0.48 to 0.80 for the DP and ranged from 0.28 to 0.64 for the HR. Furthermore, the Bland–Altman plots indicated a better agreement between the DP and the WD for estimating energy and nutrient intakes. This DP is a valid tool for measuring energy and nutrient intakes among preschoolers.